Bridging Troubled Waters : Assessing the World Bank Water Resources Strategy - Pitman, George Keith (Washington, DC: World Bank, 2013)
The comprehensive approach advocated in the 1993 water strategy is highly relevant to the sound and sustainable management of water resources. And implementing the strategy has advanced the Bank's corporate goals and mission, contributing to an emerging global consensus on water resource management. But that implementation, though broad, has been partial and uneven, with big differences across regions, countries, and subsectors. Work remains to adapt the strategy to diverse country contexts and to link water resource management to sustainable service delivery.